2011
DOI: 10.1017/s0266462311000122
|View full text |Cite
|
Sign up to set email alerts
|

Piloting the development of a cost-effective evidence-informed clinical pathway: Managing hypertension in Jordanian primary care

Abstract: The pilot represented the start of what is intended to be a healthcare process change for the country of Jordan. Issues emerged which can inform strategies to ensure a more cohesive and comprehensive approach to the cost-effective use of appropriate drugs in managing chronic disease in Jordan and countries operating in a similarly resource-constrained environment. Furthermore, our pilot highlights how richer countries with relevant experience in evidence-informed healthcare policy making can assist others in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, it is an important task to find ways to improve management of medical treatment quality and provide better medical service in infectious diseases with lower prices and higher quality. [6][7][8][9][10] Clinical pathways are an important means in the modern medical management, which gives consideration to both quality and efficiency. However, there is little literature available regarding the clinical pathway management in infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is an important task to find ways to improve management of medical treatment quality and provide better medical service in infectious diseases with lower prices and higher quality. [6][7][8][9][10] Clinical pathways are an important means in the modern medical management, which gives consideration to both quality and efficiency. However, there is little literature available regarding the clinical pathway management in infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interview participants also identified scarcity in funding as a main barrier for health services research including HTA, which is consistent with previous studies conducted in Jordan. 8,20 They reported that international organizations such as the World Bank and WHO were the main financing organizations of targeted programs.…”
Section: Funding Htamentioning
confidence: 99%
“…6 Due to a continuous increase in healthcare expenditure, researchers focused on frameworks to incorporate HTA recommendations in evidence-based treatment practice. [7][8][9][10] Given the similar purpose of informing decisionmaking, albeit in a different context, it is no surprise that the processes of relative effectiveness assessment (REA) in HTA and CG development contain considerable overlap. CGs, however, do not usually use the full HTA reports during development.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical treatment guidelines (CGs) are generally used as a tool to ensure guidance of evidence‐based medicine, aiming to advance quality of care and increasingly aiming to treat in a cost‐effective manner 6 . Due to a continuous increase in healthcare expenditure, researchers focused on frameworks to incorporate HTA recommendations in evidence‐based treatment practice 7–10 …”
Section: Introductionmentioning
confidence: 99%